Mothers’ Perception about Immunization of Children in Bangladesh - Hasan, Md Mahmudul; Gharami, Tumpa; Akter, Halima (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: Immunization is an essential public health strategy to prevent childhood diseases and enhance community health. The effectiveness of immunization programs, however, relies heavily on the acceptance and compliance of parents, particularly mothers. This study aimed to evaluate mothers' perceptions of child immunization in rural areas of Bangladesh. Methods: A cross-sectional study was conducted at the EPI center of Sher-e-Bangla Medical College Hospital in Barishal, involving 112 participants selected through convenience sampling. Data were collected via structured face-to-face interviews, utilizing a questionnaire with two sections: one on socio-demographic details and the other on mothers’ perceptions of immunization. The data were analyzed using SPSS version 26, employing descriptive statistics to summarize participant characteristics and perceptions, and inferential statistics to assess relationships among variables. Results: The average age of participants was 29.29 years (SD = 6.92). A significant positive association was observed between participants' age and their perception of immunization (r = -0.190, p = 0.045). Additionally, residential area was significantly related to immunization perception (t = -2.115, p = 0.037), and the information source also had a significant effect on perception (F = -2.115, p = 0.021). Conclusion: The study findings indicate that perceptions of immunization are significantly associated with certain demographic factors. These results highlight the need for targeted educational efforts and community-based initiatives to counter misinformation and increase awareness. The insights gained can aid policymakers, healthcare providers, and public health professionals in improving immunization rates and safeguarding the health of future generations in Bangladesh